„Zrozumieć dwujęzyczność” – doroczna konferencja dla nauczycieli pracujących z polskimi uczniami w szkołach holenderskich - Gramza, Grażyna; Steur, Agnieszka (Biuletyn Historii Wychowania, 2018)
According to statistics 160,000 Polish citizens currently live and work in the Netherlands. Half of these Polish migrants live there with their families. In April 2018, 36,000 Polish children lived in the Netherlands. Children and adolescents are required to go to local or international schools. Observing children who lived in the country for a few years and those who have just arrived, we can see recurring problems and issues. Students who do not know the Dutch language go to classes, where they only learn the language for two or three years. Within a few months, children become lazy. The curriculum that they are supposed to master is too simple, posing not enough intellectual challenges. Moreover, the first year in a new school abroad is stressful for children and adolescents. One of the major issues is the fact that teachers do not understand the processes that a child undergoes in the adaptation phase. Many schools also have an issue with the lack of knowledge regarding the development of a bilingual child. To help and support teachers, as well as parents and children, the School at the Embassy of the Republic of Poland in The Hague and the “Kreda” Foundation from Lisse organised the first “Understanding Bilingualism” conference four years ago, inviting teachers and specialists who work with Polish children every day. The conference turned out to be a resounding success and in the following years, three additional editions of the event were organised, devoted to a variety of topics.